PENGARUH LOCUS OF CONTROL, INTEGRITAS, DUE PROFESIONAL CARE DAN KEAHLIAN AUDIT PADA KUALITAS AUDIT - Pramesti, Desak Putu Putri; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 17 No 2 (2016), 2016)
The purpose of this study was to examine the effect of locus of control, integrity, due professional care and expertise audit on audit quality (case studies on public accounting firm in Bali. The study was conducted at all offices of the Office of Public Accountants in Bali of nine offices in 2015 , with the number of auditors as many as 89. in this study using saturated sample. the data analysis technique used is multiple linear regression analysis. Based on the analysis, it is known that the locus of control, integrity, diligence audit professional care and expertise effect on audit quality in Public Accounting Firm in Bali. the variable locus of control, integrity, diligence audit professional care and expertise to contribute as much as 83.4 percent on audit quality, while the remaining 16.6 percent is influenced by other variables not included in the model study.
Keywords: Locus Of Control, Integrity, Due Professional Care, Skill Audits, Quality Audits